Performance analysis of HTTP flooding attack at application layer in mobile ad-hoc network (MANET) / Muhammad Hilmi Hafizi Muhamad and Ahmad Yusri Dak - Muhamad, Muhammad Hilmi Hafizi; Dak, Ahmad Yusri (College of Computing, Informatics and Media, UiTM Perlis, 2023)
HTTP flooding is a type of distributed denial of service attack that primarily affects the application layer. It was designed for the application layer which is the interface that interacts with the application directly and provides standard web application services. An association of mobile nodes known as a mobile ad hoc network (MANET) is each node communicates with the others by passing information to them. With the assistance of a botnet, the hacker sends a huge number of packets in the direction of the web server or application. The goal of this article is to analyse HTTP flooding attacks at the application layer in MANET as well as test and simulate HTTP flooding attacks in MANET utilising three factors, namely throughput, end-to-end delay, and packet delivery ratio. Using Network Simulator 2, the simulation will be in two scenarios, and it will differ by time and by number of nodes. This research concludes that the simulations of an HTTP flooding attack produce results as expected by the DDOS attack theory after performing all the simulations, gathering all the necessary data. The HTTP flooding attack affects network efficiency, regardless of how long it lasts or how many nodes are involved. End-to-end delay outperforms throughput and packet delivery ratio as performance indicators for both scenarios that differ in time and differ by number of nodes. If both the duration and the number of nodes rise, the consequence of an HTTP flooding attack will be more efficient and effective for DDOS attack.